Why do women walk away from maternal health services in Southwest Ethiopia? A qualitative study of caregivers' and clients' perspectives - Sena Belina Kitila; Garumma Tolu Feyissa; Muluemebet Abera Wordofa (BMC, 2023)
Abstract Background Continuum of care for Maternal Health Care is continuity of care through pregnancy, childbirth, and after birth as a key strategy in reaching mothers and babies at a crucial time. Despite the widespread drop out from the continuum of care, there is limited understanding of perspectives of providers and clients about factors leading to drop out from care among women in Ethiopia. Objective The aim of this study is to explore the underlying reasons for which women walk away from maternal health services in Ethiopia care providers' and clients' perspectives. Methods The population for the study were comprised of all purposefully selected district health department deputy heads, MCH coordinators, primary health center unit directors, midwives and nurses in charge of maternity department and who have been rendering maternal health services and chosen women among those attending the MCH clinic for maternal health services in order to identify reasons for dropout from the perspective of the service users based on the established criteria. The final sample size was determined based on the level of information saturation and a total of 20 in-depth interviewees were conducted. The unstructured key informant interview (KII) guide was used to collect data to gain an in-depth understanding of the context in which continuum of care for maternal health care takes place and existing barriers. Result The main themes were identified and compared across all the transcripts to determine similarities and variations in the views of respondents. The major reasons for which women walk away from maternal health services were categorized under three main themes: healthcare system related reasons, community level barriers and individual level barriers. Interpretive analysis was conducted, and elucidations of the results follow the respective themes and verbatim that capture dominant views were considered wherever appropriate to substantiate the findings. Conclusion and recommendations Women were walk away from maternal health services because of health system, community level and individual level factors. Hence, implementing initiatives to improve both providers and clients side barriers are essential. Furthermore, we recommend more large-scale studies to digging out more context specific barriers.